A solid-state polymer electrolyte membrane, a preparation method thereof, and a solid-state lithium / sodium battery using the same

CN116742112BActive Publication Date: 2026-10-16FUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210202913.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-03
Publication Date
2026-10-16
Estimated Expiration
2042-03-03

AI Technical Summary

Technical Problem

然而普通共混对聚合物电解质离子电导率影响较弱,且往往存在相容性问题,长期充放电循环后可能出现分相,继而导致电池稳定性明显下降;接枝可在保持相容性的同时提高聚合物电导率,但受限于导离子聚合物较大的分子量,较弱的端基效应使得其对离子电导率提升的影响也十分有限;塑化剂的引入可有效提升导离子聚合物分子运动活性继而显著提高离子电导率,但往往对聚合物膜机械性能产生严重的损害

Benefits of technology

[0032] The composite all-solid polymer electrolyte membrane provided by this invention can achieve a significant improvement in its room temperature conductivity without affecting the mechanical properties of the electrolyte membrane through superplastic blending technology. The room temperature lithium/sodium ion conductivity of this composite all-solid electrolyte membrane can reach 9.2 × 10⁻⁶. -5 S/cm and 8.6×10 -5 The S/cm ratio, when applied to all-solid-state lithium/sodium batteries, enables these batteries to exhibit excellent room-temperature cycling and rate performance. The fabrication process for this composite all-solid-state polymer electrolyte membrane is simple and short, requiring minimal solvents. It only requires a single-step coating process combined with infrared irradiation and hot roll forming to produce a simple, single-layer, room-temperature conductive composite solid-state electrolyte membrane suitable for continuous production. This effectively solves the major bottleneck of room-temperature ion conduction in polymer all-solid-state batteries and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116742112B_ABST
    Figure CN116742112B_ABST
Patent Text Reader

Abstract

The application discloses a kind of all-solid-state polymer electrolyte membrane and its preparation method and the all-solid-state lithium / sodium battery of application thereof, including polymer lithium / sodium conducting matrix and lithium / sodium salt, the polymer lithium / sodium conducting matrix includes high molecular weight polymer skeleton and composite topological structure superplasticizer.The advantages of the present application are that the composite all-solid-state polymer electrolyte membrane provided by the present application can significantly improve the room temperature conductivity of the electrolyte membrane without affecting the mechanical properties of the electrolyte membrane by superplastic blending technology.The room temperature lithium / sodium ion conductivity of the composite all-solid-state electrolyte membrane can reach 9.2×10 ‑5 S / cm and 8.6×10 ‑5 S / cm respectively, and the application of the composite all-solid-state electrolyte membrane in the all-solid-state lithium / sodium battery can make the corresponding lithium / sodium ion battery exhibit excellent room temperature cycle and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium / sodium battery technology, and particularly relates to the synthesis of lithium / sodium superplasticizers, the preparation method of all-solid-state polymer electrolyte membranes, and all-solid-state lithium / sodium metal batteries using the same. Background Technology

[0002] With the increasing severity of energy and environmental issues, the widespread application of high-performance electrochemical energy storage devices, represented by lithium / sodium batteries, has become a top priority and an inevitable trend for national development and progress. However, currently widely used lithium / sodium batteries require highly flammable and volatile electrolytes, posing significant risks during charging and discharging. To achieve higher energy density and greater safety, all-solid-state lithium / sodium batteries have become an important research direction.

[0003] A major bottleneck in the development of all-solid-state lithium / sodium batteries lies in the design and fabrication of solid-state electrolytes and their compatibility with electrode materials. Among various solid-state electrolytes, polymer electrolytes offer superior flexibility, processability, designability, and interfacial compatibility, making them highly advantageous for the future development of solid-state batteries. However, commonly used ion-conducting polymers, such as PEO and PVDF-HFP, exhibit significant crystalline morphology at room temperature. The highly oriented crystalline regions within the polymer molecular chains severely restrict molecular movement, making continuous lithium / sodium ion conduction difficult. Consequently, polymer electrolytes generally suffer from low room-temperature ionic conductivity, hindering stable ion conduction. Common methods to improve polymer ionic conductivity include polymer blending, grafting, or the addition of plasticizers to create composite solid-state electrolytes. However, conventional blending has a weak effect on the ionic conductivity of polymer electrolytes and often presents compatibility issues. Long-term charge-discharge cycles may lead to phase separation, resulting in a significant decrease in battery stability. Grafting can improve polymer conductivity while maintaining compatibility, but its limited effect on ionic conductivity improvement is constrained by the large molecular weight of the ion-conducting polymer and the weak end-group effect. The introduction of plasticizers can effectively enhance the molecular mobility of the ion-conducting polymer, thereby significantly improving ionic conductivity, but it often severely damages the mechanical properties of the polymer membrane. Therefore, designing solid-state polymer electrolytes with high ionic conductivity and excellent interfacial stability while maintaining membrane self-support performance remains a significant research challenge. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings and deficiencies of existing technologies by providing an all-solid-state polymer electrolyte membrane, its preparation method, and an all-solid-state lithium / sodium battery using the same. This solid-state electrolyte membrane possesses both high room-temperature ionic conductivity and strong charge-discharge stability without sacrificing its mechanical strength.

[0005] To achieve the above objectives, a first aspect of the present invention is to provide an all-solid-state polymer electrolyte membrane, the technical solution of which includes a polymer lithium / sodium matrix and a lithium / sodium salt, wherein the polymer lithium / sodium matrix includes a high molecular weight polymer backbone and a polyether / polyeneimide superplasticizer having a linear-branched composite topology.

[0006] The aforementioned high molecular weight polymer backbone provides mechanical strength and self-support for the composite electrolyte membrane; the composite topological superplasticizer inhibits polymer crystallization through blending and plasticization mechanisms, optimizing the room temperature ionic conductivity of the electrolyte; lithium / sodium salts provide sufficient lithium / sodium ions and are uniformly distributed in the polymer matrix, forming a coordination ion-conducting system with the above two components.

[0007] Preferably, the polymer backbone is selected from one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyvinyl acetate, and polylactic acid.

[0008] Preferably, the number-average molecular weight of the organic polymers selected for the polymer backbone is between 100,000 and 2,000,000.

[0009] Preferably, the superplasticizer is a polyether polymer with a composite topological structure, selected from one or more of the following: "dumbbell-shaped" polyether IROP-A, "mop-shaped" polyether IROP-B, polyether-polyethyleneimine star-shaped molecule PUC-A, and polyether-polyethyleneimine brush molecule PUC-B, with a molecular weight of 11,000 to 2,000,000.

[0010] Preferably, the nonlinear unit mass percentage of the above-mentioned polymeric superplasticizer is 10% to 100%.

[0011] Preferably, the polymer backbone and the superplasticizer together form the electrolyte membrane polymer lithium-conducting matrix.

[0012] Preferably, the mass ratio between the polymer backbone and the superplasticizer is 1:0.5 to 1:3.

[0013] Preferably, the lithium salt is selected from one or more of lithium bis(oxalato)borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium difluorooxalatoborate, and lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide.

[0014] Preferably, the sodium salt is selected from one or more of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl)imide, and sodium bis(fluorosulfonyl)imide.

[0015] Preferably, the molar ratio of the above lithium / sodium salt to the polymer lithium / sodium matrix lithium / sodium repeating unit is 1:10 to 20.

[0016] Preferably, the thickness of the all-solid polymer electrolyte membrane is 50–200 μm.

[0017] Specifically, the lithium / sodium repeating unit here refers to a polymeric segment repeating unit containing groups capable of coupling-decoupling with lithium / sodium ions.

[0018] During the charge-discharge cycle of the assembled half-cell, the superplasticizer interacts with the macromolecular lithium-conducting backbone through the plasticizing blending mechanism. Its nonlinear topology can effectively restrict the orientation of the regular segments of the lithium-conducting polymer and thus inhibit the crystallization of the composite film, while the linear structure inhibits crystallization and causes micro-entanglement, thus ensuring the mechanical strength of the electrolyte membrane.

[0019] In addition, the ion-promoting groups, represented by tertiary amines, contained in superplasticizers can effectively guide the dissociation of lithium / sodium ions with the corresponding anions, thereby effectively improving the migration efficiency of lithium / sodium ions and thus enhancing charge-discharge stability.

[0020] A second aspect of the present invention is to provide a method for preparing an all-solid-state polymer electrolyte membrane, comprising the following steps:

[0021] S1. Dissolve the high molecular weight polymer backbone, the composite topology superplasticizer and the lithium / sodium salt in a solvent to prepare a homogeneous polymer concentrated solution.

[0022] S2. The homogeneous polymer concentrated solution is slowly poured onto release paper using a casting method, and an electrolyte wet film is prepared by scraping with a doctor blade. The electrolyte dry film is then obtained by drying and desolvating with infrared radiation. The thickness of the polymer electrolyte wet film is controlled by the doctor blade.

[0023] S3. The polymer electrolyte dry film is subjected to hot rolling to finally obtain the polymer electrolyte film.

[0024] The entire process described above was carried out in a drying room with a relative humidity of less than 20%.

[0025] A further provision is that the solvent in step S1 is selected from one or more of anhydrous acetonitrile, anhydrous N-methylpyrrolidone, anhydrous N,N-dimethylformamide, anhydrous acetone, and anhydrous isopropanol.

[0026] Preferably, the heating temperature is 50–90°C and the rolling thickness is 20–200 μm.

[0027] Preferably, the thickness of the composite solid electrolyte membrane prepared by the above casting and coating method is 20-250 μm.

[0028] A third aspect of the present invention is to provide a polymer all-solid-state lithium / sodium battery comprising the above-described all-solid-state polymer electrolyte membrane.

[0029] Preferably, the positive electrode material of the above-mentioned lithium battery is any one of lithium iron phosphate, lithium cobalt oxide and NCM ternary positive electrode materials; the negative electrode material is lithium metal.

[0030] Preferably, the positive electrode material of the above-mentioned sodium battery is any one of sodium iron phosphate, sodium vanadium phosphate, and sodium nickel manganese phosphate; the negative electrode material is sodium metal.

[0031] The beneficial effects of this invention are as follows:

[0032] The composite all-solid polymer electrolyte membrane provided by this invention can achieve a significant improvement in its room temperature conductivity without affecting the mechanical properties of the electrolyte membrane through superplastic blending technology. The room temperature lithium / sodium ion conductivity of this composite all-solid electrolyte membrane can reach 9.2 × 10⁻⁶. -5 S / cm and 8.6×10 -5 The S / cm ratio, when applied to all-solid-state lithium / sodium batteries, enables these batteries to exhibit excellent room-temperature cycling and rate performance. The fabrication process for this composite all-solid-state polymer electrolyte membrane is simple and short, requiring minimal solvents. It only requires a single-step coating process combined with infrared irradiation and hot roll forming to produce a simple, single-layer, room-temperature conductive composite solid-state electrolyte membrane suitable for continuous production. This effectively solves the major bottleneck of room-temperature ion conduction in polymer all-solid-state batteries and has broad application prospects. Attached Figure Description

[0033] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, obtaining other drawings based on these drawings without creative effort still falls within the scope of the present invention.

[0034] Figure 1 Ionic conductivity of composite all-solid-state polymer electrolyte membrane at different temperatures;

[0035] Figure 2 The charge-discharge (voltage-specific capacity) curves (a) of lithium iron phosphate / lithium metal batteries assembled from the composite all-solid electrolyte membranes prepared in Example 1 and Comparative Example 1 at 0.1C at room temperature and the room temperature rate cycle discharge curve (b) of Example 1 are shown.

[0036] Figure 3 The lithium iron phosphate all-solid-state battery assembled from the composite all-solid-state electrolyte membrane prepared in Example 1 exhibits the rate discharge performance at room temperature and the constant current long-cycle performance curves at 0.1C. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings.

[0038] In Examples 1-12 and Comparative Examples 2-5, organic-inorganic composite solid electrolyte membranes were prepared by the following methods:

[0039] (1) Weigh 0.94g of a solid containing a polymer lithium-conducting matrix and lithium salt and dissolve it in 3g of acetonitrile. Stir thoroughly at room temperature for 12h to form a homogeneous polymer concentrated solution.

[0040] (2) In a drying room with a relative humidity of less than 20%, the above concentrated solution is poured onto release paper and quickly coated with a doctor blade to obtain a polymer electrolyte wet film; the wet film is dried by infrared radiation to remove residual solvent and obtain an electrolyte dry film; the electrolyte dry film is hot rolled at a heating environment of 50-90℃ and a rolling thickness of 20-200μm to obtain the desired all-solid polymer electrolyte film.

[0041] In Comparative Example 1, the solvent acetonitrile was replaced with N-methylpyrrolidone, and the parameters of the remaining steps were the same, so they will not be described again.

[0042] Example 1

[0043] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, IROP-A, and lithium bis(trifluoromethanesulfonyl)imide. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of IROP-A is 11,000, with a linear ether oxygen structure to branched ether oxygen structure mass ratio of 1:0.1; the mass ratio of PEO to IROP-A is 1.5:1; calculated by molar ratio, the ratio of lithium bis(trifluoromethanesulfonyl)imide to ether oxygen units in PEO and IROP-A is 1:18.

[0044] Example 2

[0045] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, IROP-A, and lithium bis(fluorosulfonyl)imide. The number-average molecular weight of PEO is 600,000; the number-average molecular weight of IROP-A is 2,200, with a linear ether oxygen structure to branched ether oxygen structure mass ratio of 1:0.1; the mass ratio of PEO to IROP-A is 1.5:1; calculated by molar ratio, the ratio of lithium bis(fluorosulfonyl)imide to ether oxygen units in PEO and IROP-A is 1:18.

[0046] Example 3

[0047] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, IROP-B, and lithium perchlorate. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of IROP-B is 9,000, with a linear ether oxygen structure to branched ether oxygen structure mass ratio of 1:0.125; the mass ratio of PEO to IROP-B is 1.5:1; and calculated by molar ratio, the ratio of lithium perchlorate to ether oxygen units in PEO and IROP-B is 1:18.

[0048] Example 4

[0049] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, IROP-A, and lithium bis(trifluoromethanesulfonyl)imide. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of IROP-A is 12,500, with a linear ether oxygen structure to branched ether oxygen structure mass ratio of 1:0.25; the mass ratio of PEO to IROP-A is 1.5:1; calculated by molar ratio, the ratio of lithium bis(trifluoromethanesulfonyl)imide to ether oxygen units in PEO and IROP-A is 1:18.

[0050] Example 5

[0051] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, IROP-A, and lithium bis(trifluoromethanesulfonyl)imide. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of IROP-A is 15,000, with a linear ether oxygen structure to branched ether oxygen structure mass ratio of 1:0.5; the mass ratio of PEO to IROP-A is 1.5:1; calculated by molar ratio, the ratio of lithium bis(trifluoromethanesulfonyl)imide to ether oxygen units in PEO and IROP-A is 1:18.

[0052] Example 6

[0053] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, IROP-A, and lithium bis(trifluoromethanesulfonyl)imide. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of IROP-A is 17,500, with a linear ether oxygen structure to branched ether oxygen structure mass ratio of 1:0.75; the mass ratio of PEO to IROP-A is 1.5:1; calculated by molar ratio, the ratio of lithium bis(trifluoromethanesulfonyl)imide to ether oxygen units in PEO and IROP-A is 1:18.

[0054] Example 7

[0055] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, IROP-A, and lithium bis(trifluoromethanesulfonyl)imide. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of IROP-A is 20,000, with a linear ether oxygen structure to branched ether oxygen structure mass ratio of 1:1; the mass ratio of PEO to IROP-A is 1.5:1; calculated by molar ratio, the ratio of lithium bis(trifluoromethanesulfonyl)imide to ether oxygen units in PEO and IROP-A is 1:18.

[0056] Example 8

[0057] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, PUC-APUC-A, and lithium bis(trifluoromethanesulfonyl)imide. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of PUC-A is 190,000, with the linear PEG arm having a molecular weight of 500, and its mass ratio to the core layer BPEI is 12:7; the mass ratio of PEO to PUC-A is 1.5:1; calculated by molar ratio, the ratio of lithium bis(trifluoromethanesulfonyl)imide to the ether oxygen units in PEO and PUC-A is 1:18.

[0058] Example 9

[0059] The composite all-solid-state electrolyte membrane in this embodiment includes PEO, PUC-B, and lithium bis(trifluoromethanesulfonyl)imide. The number-average molecular weight of PEO is 1 million; the number-average molecular weight of PUC-B is 2.2 million, with the linear PEG brush having a molecular weight of 500 and a mass ratio of PEG-brush-B to the main chain LPEI of 1:0.1; the mass ratio of PEO to PEG-brush-BPEI is 1.5:1; calculated by molar ratio, the ratio of lithium bis(trifluoromethanesulfonyl)imide to the ether oxygen units in PEO and PUC-B is 1:18.

[0060] Example 10

[0061] Unlike Example 1, in the preparation of the polymer film in Example 10, the mass ratio of PEO to IROP-A was adjusted to 2:1 while keeping the mass constant. All other aspects were the same as in Example 1 and will not be repeated here.

[0062] Example 11

[0063] Unlike Example 1, in the preparation of the polymer film in Example 11, the mass ratio of PEO to IROP-A was adjusted to 3:1 while keeping the mass constant. All other aspects were the same as in Example 1 and will not be repeated here.

[0064] Example 12

[0065] Unlike Example 1, in the preparation of the polymer film in Example 12, the mass ratio of PEO to IROP-A was adjusted to 0.75:1 while keeping the mass constant. All other aspects were the same as in Example 1 and will not be repeated here.

[0066] Example 13

[0067] Unlike Example 1, in the preparation of the polymer film in Example 13, sodium trifluoromethanesulfonate was used instead of lithium bis(trifluoromethanesulfonylimide), while the rest was the same as in Example 1.

[0068] Example 14

[0069] Unlike Example 13, in the preparation of the polymer film in Example 14, the mass ratio of PEO to IROP-A was adjusted to 2:1, while the rest was the same as in Example 13.

[0070] Example 15

[0071] Unlike Example 13, in the polymer membrane preparation process of Example 15, the sodium salt was changed from sodium trifluoromethanesulfonate to sodium perchlorate, while the rest was the same as in Example 13.

[0072] Example 46

[0073] Unlike Example 13, in the polymer film preparation process of Example 26, the superplasticizer was changed from IROP-A to PUC-B, while the rest was the same as in Example 13.

[0074] Comparative Example 1

[0075] Unlike Example 1, no superplasticizer component was added in Comparative Example 1. The polymer film was composed only of PEO with a number average molecular weight of 1 million and lithium bis(trifluoromethanesulfonyl)imide in a lithium to ether oxygen unit molar ratio of 1:18. All other aspects were the same as in Example 1.

[0076] Comparative Example 2

[0077] Unlike Example 1, the electrolyte membrane polymer backbone in Comparative Example 2 is PVDF-HFP, while the rest is the same as in Example 1.

[0078] Comparative Example 3

[0079] Unlike Example 1, the molar ratio of lithium bis(trifluoromethanesulfonyl)imide to polymer ether oxygen unit in the polymer film of Comparative Example 3 is 1:30, while the rest is the same as in Example 1.

[0080] Comparative Example 4

[0081] Unlike Example 1, the molar ratio of lithium bis(trifluoromethanesulfonyl)imide to polymer ether oxygen unit in the polymer film of Comparative Example 4 is 1:20, while the rest is the same as in Example 1.

[0082] Comparative Example 5

[0083] Unlike Example 1, Comparative Example 5 was prepared by blending a conventional polymeric plasticizer (PEG with a number average molecular weight of 10,000) with PEO and lithium bis(trifluoromethanesulfonyl)imide at a lithium to ether oxygen unit molar ratio of 1:18. All other aspects were the same as in Example 1.

[0084] Comparative Example 6

[0085] Unlike Example 13, no superplasticizer component was added in Comparative Example 6. The polymer film was composed only of PEO with a number average molecular weight of 1 million and sodium trifluoromethanesulfonate in a sodium to ether oxygen unit molar ratio of 1:18. All other aspects were the same as in Example 13.

[0086] Comparative Example 7

[0087] Unlike Example 13, the electrolyte membrane polymer backbone in Comparative Example 7 is PVDF-HFP, while the rest is the same as in Example 13.

[0088] Comparative Example 8

[0089] Unlike Example 13, in Comparative Example 8, the molar ratio of sodium trifluoromethanesulfonate to polymer ether oxygen unit in the polymer membrane was 1:30, while the rest were the same as in Example 13.

[0090] Comparative Example 9

[0091] Unlike Example 13, in Comparative Example 9, the molar ratio of sodium trifluoromethanesulfonate to polymer ether oxygen unit was 1:40, while the rest were the same as in Example 13.

[0092] Test Example 1

[0093] A blocking electrode with a stainless steel gasket / all-solid-state composite electrolyte / stainless steel gasket structure was constructed. Using electrochemical impedance spectroscopy and relevant formulas, the ionic conductivity of the all-solid-state polymer electrolyte membranes prepared in the above examples and comparative examples was tested at different temperatures. The test results for Examples 1-5 and Comparative Examples 1-5 are shown in Table 1. Figure 1 .

[0094] Table 1. Ionic conductivity of the composite all-solid-state electrolytes in Examples 1-5 and Comparative Examples 1-5 at different temperatures.

[0095]

[0096]

[0097] The test results show that the room temperature ionic conductivity of the composite all-solid polymer electrolyte prepared in Example 1 can exceed 9 × 10⁻⁶. -5 The S / cm conductivity is 11 times higher than that of the comparative example without superplasticizer, and its ionic conductivity at different temperatures is also higher than that of comparative example 1, indicating strong practical application value. Furthermore, comparison with other embodiments shows that composite solid electrolyte membranes prepared using polymers within the scope defined by this invention, different types of superplasticizers, and different component ratios all exhibit high ionic conductivity.

[0098] Test Example 2

[0099] The composite all-solid-state electrolyte membrane prepared above was assembled into a lithium iron phosphate / Li metal half-cell, and its charge-discharge cycle performance at 0.1C at room temperature was tested. The charge-discharge test results of Example 1 and Comparative Example 1 are as follows: Figure 1 As shown in the figure, the charge-discharge performance of other embodiments and comparative examples is shown in Table 2. It can be seen from the figure that the lithium iron phosphate solid-state full battery assembled using the organic-inorganic composite solid-state electrolyte prepared according to this invention has higher capacity, better capacity retention, and higher coulombic efficiency than the comparative electrolyte.

[0100] Table 2 Cycle performance test of lithium iron phosphate / Li batteries assembled with composite solid electrolyte membranes

[0101]

[0102] Test Example 3

[0103] The polymer electrolyte membranes synthesized in Examples 13-16 and Comparative Examples 6-9 were assembled into sodium vanadium phosphate / Na metal half-cells and their charge-discharge cycle performance at 0.1C at room temperature was tested. The charge-discharge performance of some examples and comparative examples is shown in Table 3.

[0104] Table 3 Cycle performance test of sodium vanadium phosphate / Na batteries assembled with composite solid electrolyte membranes

[0105]

[0106] The above description discloses only preferred embodiments of the present invention and should not be construed as limiting the scope of the present invention. Therefore, equivalent variations made in accordance with the claims of the present invention are still within the scope of the present invention.

Claims

1. An all-solid-state polymer electrolyte membrane, characterized in that: It includes a polymer lithium-conducting / sodium matrix and a lithium / sodium salt, wherein the polymer lithium-conducting / sodium matrix includes a high molecular weight polymer backbone and a polyether / polyene imine superplasticizer having a linear-branched composite topology; The polyether / polyeneimide superplasticizer with a linear-branched composite topology is selected from one or more of the following: dumbbell-shaped polyethylene oxide prepared by ionic ring-opening polymerization, mop-shaped polyethylene glycol, polyethylene glycol-polyethyleneimide star molecules modified with hydroxyl-terminated polyurethane, and polyethylene glycol-polyethyleneimide molecular brushes. Their structures and names are shown in formulas (1)-(4), respectively: Equation (1) Equation (2) Equation (3) Equation (4); The high molecular weight polymer backbone is selected from one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyvinyl acetate, and polylactic acid.

2. The all-solid-state polymer electrolyte membrane according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium bis(oxalato)borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, and lithium difluorooxalatoborate. The sodium salt is selected from one or more of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl)imide, and sodium bis(fluorosulfonyl)imide.

3. The all-solid-state polymer electrolyte membrane according to claim 1, characterized in that: The molar ratio of the lithium / sodium salt to the repeating lithium / sodium unit in the polymer lithium / sodium matrix is ​​1:10~20.

4. The all-solid-state polymer electrolyte membrane according to claim 1, characterized in that: The thickness of the all-solid polymer electrolyte membrane is 20~250 μm.

5. A method for preparing an all-solid-state polymer electrolyte membrane as described in any one of claims 1-4, characterized in that... Includes the following steps: S1. Dissolve the high molecular weight polymer backbone, the composite topology superplasticizer and the lithium / sodium salt in a solvent to prepare a homogeneous polymer concentrated solution. S2. The homogeneous polymer solution is slowly poured onto release paper using a casting method, and an electrolyte wet film is obtained by scraping and then dried and desolventized by infrared radiation to obtain an electrolyte dry film. S3. The electrolyte dry film is subjected to hot rolling to finally obtain the polymer electrolyte film.

6. The method for preparing the all-solid-state polymer electrolyte membrane according to claim 5, characterized in that: The solvent in step S1 is selected from one or more of anhydrous acetonitrile, anhydrous N-methylpyrrolidone, anhydrous N,N-dimethylformamide, anhydrous acetone, and anhydrous isopropanol.

7. A polymer all-solid-state lithium / sodium battery, characterized in that... It includes the all-solid polymer electrolyte membrane as described in any one of claims 1-4.

8. The polymer all-solid-state lithium / sodium battery according to claim 7, characterized in that: The positive electrode material of the polymer all-solid-state lithium battery is any one of lithium iron phosphate, lithium cobalt oxide and NCM ternary positive electrode materials, and its negative electrode is a metallic lithium negative electrode. Alternatively, the positive electrode material of the polymer all-solid-state sodium battery can be any one of sodium iron phosphate, sodium vanadium phosphate, or sodium nickel manganese phosphate, and its negative electrode is a metallic sodium negative electrode.

Citation Information

Patent Citations

  • Method for preparing all-solid-state polymer electrolyte through in-situ thermal initiation and application

    CN111944099A

  • Polymer solid electrolyte membrane, preparation method thereof and all-solid-state battery

    CN112993396A

  • Ion conductive polymer solid electrolyte

    JP2011046784A